2011
DOI: 10.1174/217119711794394671
|View full text |Cite
|
Sign up to set email alerts
|

Propiedades psicométricas de la Escala de Identidad Ambiental (EID)

Abstract: EID) ha sido propuesta por Clayton para estudiar la relación entre identidad y naturaleza. A pesar de ser citada en varias publicaciones, pocas veces ha sido sometida a análisis psicométrico. El objetivo principal de este estudio ha sido analizar el cumplimiento de criterios de validez de constructo y convergente de esta escala. Para ello se recurrió a una muestra universitaria de 282 personas quienes completaron un cuestionario compuesto por la EID, y otras medidas afines, como

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 25 publications
(12 reference statements)
1
18
0
11
Order By: Relevance
“…As expected, EID scores are strongly correlated with environmental concern, values, behavior, and behavioral intention (Clayton, 2003;Matsuba et al, 2012;Olivos & Aragonés, 2011;Scopelliti et al, 2018;Tam, 2013b;Watson, Hegtvedt, Johnson, Parris, & Subramanyam, 2017). Of particular note for the present paper, Kiesling and Manning (2010) found that EID was positively correlated with several scales related to gardening, including pro-environmental gardening behavior, engagement with natural processes, and an overall sense of gardening identity.…”
Section: Measurement Of Environmental Identitysupporting
confidence: 72%
See 2 more Smart Citations
“…As expected, EID scores are strongly correlated with environmental concern, values, behavior, and behavioral intention (Clayton, 2003;Matsuba et al, 2012;Olivos & Aragonés, 2011;Scopelliti et al, 2018;Tam, 2013b;Watson, Hegtvedt, Johnson, Parris, & Subramanyam, 2017). Of particular note for the present paper, Kiesling and Manning (2010) found that EID was positively correlated with several scales related to gardening, including pro-environmental gardening behavior, engagement with natural processes, and an overall sense of gardening identity.…”
Section: Measurement Of Environmental Identitysupporting
confidence: 72%
“…This scale has strong internal reliability and test-retest reliability. The principal components analysis has typically found only a single dominant factor, though occasionally a more complex structure emerges; for example, Fritsche and Häfner (2012) found two factors among German students, one interpreted as reflecting contact with nature and one as reflecting self-definition; Olivos and Aragonés (2011) identified four factors, including self-definition, environmental enjoyment, environmental appreciation, and environmentalism. In known-groups comparisons, Clayton (2003) found significant differences between environmental studies students and a comparison group of students in the U.S.; Matsuba et al (2012) found that environmentalists scored significantly higher on EID than did a comparison group in Canada; while Scopelliti et al (2018), in a cross-national study, found that European leaders who were distinguished by their actions for biodiversity scored higher on environmental identity than did similarly-situated individuals who were not known for such actions.…”
Section: What Is Environmental Identity?mentioning
confidence: 99%
See 1 more Smart Citation
“…Worth highlighting among the multiple approaches to measuring the relationship between the self and nature is the connectedness to nature scale (CNS) developed by Mayer and Frantz (2004) owing to its frequent use (e.g., Brügger et al, 2011; Corraliza and Bethelmy, 2011; Olivos and Aragonés, 2011; Cervinka et al, 2012; Matas-Terrón and Elósegui-Bandera, 2012; Olivos et al, 2013; Olivos and Aragonés, 2014; Zhang et al, 2014). This scale comprises 13 items with a graded response, in which participants must be situated along a continuum of five points.…”
Section: Introductionmentioning
confidence: 99%
“…As a comparison group, we used data from different studies in which the Connectedness to Nature scale was administered in Spanish to students of psychology [ 37 , 38 , 39 , 40 , 7 , 8 ]. By unifying these databases, a total group of 1504 participants was obtained, of which 1153 were women and 351 were men, with a mean age of 23.15 years (SD = 7.45).…”
Section: Methodsmentioning
confidence: 99%